Optimizing the Performance of the General Crimes Unit of the Criminal Investigation Unit in Resolving Theft Cases in the Legal Area of ​​Kendal Police - Asward Raistra (Tanggon Kosala, 2022)
The number of cases of motor vehicle theft (Curanmor) in the community of Kab. Kendal from year to year has increased in terms of quantity and has developed in terms of the motives. The Kendal Police as a state institution that has the main function and authority to enforce the law, is required to improve the performance of its staff in handling cases of “curanmor” in the community. Based on the results of the research conducted, the resolvement of “curanmor” cases by the general criminal unit of the Kendal Police Criminal Investigation Unit, so far has not been optimal, as there are still many unresolved cases of “curanmor”. There are still limitations on the condition of organizational resources, especially from the aspect of the quality of personnel competence and the implementation of investigative management that is not yet optimal, which is the cause of the non-optimal performance of solving the “curanmor” case by the Kendall Police. On this basis, it is necessary to make efforts to optimize the performance of the general criminal unit Satreskrim in solving the “curanmor” case through improving the quality of personnel competence, as well as improving aspects of investigative management, especially in the aspects of planning and implementation.